Do subsidy increases promote or inhibit innovation? Evidence from Chinese enterprises listed on the SSE STAR Market - Xiaobao, Peng; Wu, Jian (Chinese management studies, 2024)
Purpose This study aims to comprehensively investigate the relationship between government subsidies and innovation performance in Chinese enterprises listed on the SSE STAR Market. Design/methodology/approach An unbalanced sample, covering 285 observations in 215 enterprises listed on the SSE STAR Market from 2019 to 2020, was used to explore the relationships between government subsidies, R&D investment, CEO shareholding and innovation performance. Counterfactual analysis is added for robustness testing. Findings Empirical evidence confirms that government subsidies have an inverted U-shaped relationship with R&D investment and innovation performance. Meanwhile, R&D investment is a mediating variable between government subsidies and innovation performance. Moreover, CEO shareholding plays a moderating role between government subsidies and R&D investment. The higher the CEO ownership, the steeper the inverted U-shaped relationship. Practical implications The government should introduce a dynamic mechanism to reasonably control subsidy amounts and strengthen the supervision of subsidy use. Enterprise managers should be aware of how incentives affect the firm’s innovation and implement a coordinated development of government subsidy policies and internal enterprise governance. Originality/value This study adds new empirical evidence for the relationship between government subsidies and enterprise innovation performance. The risk incentive provided by stock options is an important micro mechanism to compensate for the lack of government subsidies. The study identifies ways to promote firm innovation based on the synergistic effect of internal and external mechanisms.